LIQUIDITY, PROFITABILITY, AND DIVIDEND DECISIONS: PANEL EVIDENCE FROM INDONESIA’S INFRASTRUCTURE FIRMS - Atika Rahmi; Raisya Puspa Septiani (Jurnal Media Akademik (JMA), 2026)
This study examines the relationship between liquidity, profitability, and dividend policy in infrastructure sector firms listed on the Indonesia Stock Exchange during the 2022–2024 period. Dividend policy, proxied by the Dividend Payout Ratio (DPR), remains a strategic financial decision that reflects management’s stance toward internal financing and shareholder returns. Using panel data obtained from published annual financial statements, this research employs multiple regression analysis estimated through EViews to assess the effect of liquidity, measured by the Current Ratio (CR), and profitability, measured by Return on Assets (ROA), on dividend policy. The empirical results indicate that both CR and ROA exhibit positive coefficients; however, neither variable demonstrates a statistically significant effect on DPR, either individually or jointly. The findings suggest that dividend decisions among infrastructure firms are not primarily driven by short-term liquidity positions or accounting profitability. This outcome lends support to dividend irrelevance arguments and residual dividend considerations, particularly in capital-intensive sectors where retained earnings are prioritized for long-term investment. The study implies that managers may adopt a cautious dividend strategy, emphasizing financial flexibility rather than signaling or immediate shareholder distribution. These results contribute to the ongoing debate on dividend policy in emerging markets and provide practical insights for investors and policymakers regarding the financial behavior of infrastructure firms.